Two extraction-free reverse transcription loop-mediated isothermal amplification assays for detection of SARS-CoV-2 - Meng Yee Lai (BMC, 2021)
Abstract Background Current assays for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rely on time consuming, costly and laboratory based methods for virus isolation, purification and removing inhibitors. To address this limitation, we propose a simple method for testing RNA from nasopharyngeal swab samples that bypasses the RNA purification step. Methods In the current project, we have described two extraction-free reverse transcription loop-mediated isothermal amplification (RT-LAMP) assays for the detection of SARS-CoV-2 by using E gene and RdRp gene as the targets. Results Here, results showed that reverse transcription loop-mediated isothermal amplification assays with 88.4% sensitive (95% CI: 74.9–96.1%) and 67.4% sensitive (95% CI: 51.5–80.9%) for E gene and RdRp gene, respectively. Conclusion Without the need of RNA purification, our developed RT-LAMP assays for direct detection of SARS-CoV-2 from nasopharyngeal swab samples could be turned into alternatives to qRT-PCR for rapid screening.